Contrast media induced nephropathy: case series and review of the literature focusing on management - Marciyasa, Putu Agus; Kandarini, Yenny; Mahadita, Gede Wira; Ayu, Nyoman Paramita (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundContrast media administration during diagnostic and invasive procedures in high risk patients for nephrotoxicity is a common problem in clinical practice. Radiological procedures using intravascular iodinated contrast injection media have been widely used for therapeutic purposes. Contrast-induced nephropathy (CIN) is a serious complication of angiographic procedures and results from administration of contrast media (CM), which increases morbidity and mortality rates. Case Description We present these 10 cases with high risk of CIN and diverse characteristics. A new generation iso-osmolar CM (iodixanol) was administered in these cases. Three of the cases experienced CIN events, where one patient experienced an improvement in his condition, but two other patients experienced complications and eventually died due to the underlying disease. The other 6 cases did not experience CIN after receiving CM, which was due to better preparation beforehand. One patient with a history of regular hemodialysis, underwent immediate post-operative dialysis with CM, and no evaluation of the incidence of CIN was required. Conclusion Of the 10 cases observed, 3 of them experienced CIN which was caused by the severity of the patient’s condition and lack of preparation time before the CM procedure. Management of CIN is complex, starting from the pre-treatment evaluation until 72 hours or more after the CM procedure. This case series suggests that even new generation CM (including iodixanol) may be severely nephrotoxic, when administered to high risk patients. The amount of CM given must be below the maximum limit and adjusted to the patient’s condition. Additionally, we review the complex mechanisms involved in management of CM nephrotoxicity.